Kesiapan Visualisasi Data Kemiskinan sebagai Rujukan dalam Perencanaan Pengembangan Kebijakan - Dwi Yuniarto; Muhammad Agreindra Helmiawan; Yan Yan Sofiyan (STMIK Sumedang, 2019)
This study aims to find out what factors influence the readiness of data visualization that is used as a reference for policy development planning. The important role associated with a data visualization requires responses from several users, considering that in the process of procurement and construction of data visualization sometimes an institution does not pay attention to readiness studies, moreover it is intended to visualize poverty data. The method in this study there are three stages, which consist of literature review, operationalization, and writing of research reports. The research model used is the Technology Readiness Index model from Parasuraman with motivators, optimism, innovation, inhibitors, discomfort, insecurity and output readiness variables. The results obtained stated that insecurity factors had an effect on readiness. Given the respondents from various elements with different educational backgrounds and also many gaps arise in its application, it is necessary to choose respondents wisely to get more valid results